Floridians’ Engagement in Landscape Best Practices to Protect Water Resources: Information from a 2018 Survey - Laura A. Sanagorski Warner; Esen Momol; Claire Lewis; Tom Wichman; Wendy Wilber; A.J. Reisinger (EDIS)
Extension programs are most effective when informed by a deep understanding of the target audience. To guide programs in Florida’s managed landscapes, especially pertaining to water quality and conservation, faculty from the UF/IFAS Center for Landscape Conservation and Ecology conduct an annual statewide survey. The survey gathers data that includes common landscape elements, neighborhood characteristics, engagement in irrigation and fertilizer best practices, and learning preferences. This new 5-page publication of the UF/IFAS Department of Agricultural Education and Communication presents highlights from the 2018 statewide survey with recommendations for how to use the information. Written by Laura A. Warner, Esen Momol, Claire Lewis, Tom Wichman, Wendy Wilber, and A. J. Reisinger. https://edis.ifas.ufl.edu/wc345